ANALISIS PENERAPAN PAPAN PUZZLE INTERAKTIF PADA PEMBELAJARAN IPAS MATERI BAGIAN TUBUH TUMBUHAN DI KELAS IV SD - Sianturi, Yulia; Sijabat, Amelia Cindi; Tambunan, Maria Renatha; Putri, Rinda Tri; Pranoto, Shakira Zahra; Simamora, Enisa (Jurnal Merah Putih Sekolah Dasar, 2025)
The focus of this observation is to describe the use of interactive puzzle boards in helping fourth-grade students understand the parts of plants and their functions. Descriptive qualitative observation methods were used to directly observe how this media influenced learning activities, student responses, and conceptual understanding during the learning process. Before the media was used, most students were unable to correctly name plant parts and showed little engagement during learning activities. After the interactive puzzle was implemented, students were more active in assembling puzzle pieces, discussing, and connecting images with the concepts being studied. The questionnaire results showed an increase in student interest and enjoyment during the learning process. In addition, learning outcomes improved significantly, with students' scores, which were previously in the range of 40-80, changing to 80-100 after the use of the media. These findings indicate that interactive puzzles are able to create real and more interesting learning experiences that foster creativity, interest, and understanding of the material among students.